Hadith #4267 - Sunan Abi Dawud - al-Ahnaf bin Qays الأحنف بن قيس بن معاوية; al-Hasan al-Basri الحسن البصري; Ayoub al-Sakhtiyani أيوب السختياني; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: A Muslim’s best property will soon be sheep which he will take to the tops of the mountains and the places where the rain falls, fleeing with his religion from the civil strife (fitan).
Grade: Sahih

Hadith #4606 - Sunan Abi Dawud - al-Ahnaf bin Qays الأحنف بن قيس بن معاوية; Ibn Jurayj ابن جريج; ibn Mas'ud; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Atyq سليمان بن عتيق; Tlq bin Habib al-Nzy al-Bsry طلق بن حبيب; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
If any one introduces into this affair of ours anything which does not belong to it, it is rejected. Ibn `Isa said: The Prophet (ﷺ) said: If anyone practices any action in a way other than our practice, it is rejected.
Grade: Sahih

Hadith #4721 - Sunan Abi Dawud - al-'Abbas ibn 'Abd al-Muttalib; al-Ahnaf bin Qays الأحنف بن قيس بن معاوية; al-Walid bin Abi Thwr Sm' الوليد بن أبي ثور; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Smak bin Hrb bin Aws سماك بن حرب بن أوس (Sunan Abi Dawud)
People will continue to ask one another(questions) till this is pronounced: Allah created all things, but who created Allah ? Whoever comes across anything of that, he should say: I believe in Allah.
Grade: Sahih